(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This present study involved the application and comparison of nanoscale particles in remediation for contaminated heavy metal effluent discharge. It aimed to investigate the removal efficiency and kinetic removal rate of the heavy metals including lead, chromium, and cadmium in silk dyeing effluent discharge by using nano and microscale of ZVI and ZnO particles. The contaminated samples were collected and later treated by one of the particles in the laboratory at 25 ºC. The mixtures were incubated for the required period before the heavy metal concentrations were measured. The overall results showed that the optimum dosage of all four particle types for heavy metal treatments was 60 mg/L with an optimal time of 60 minutes. The experiments with nZVI demonstrated the highest removal efficiency for all heavy metal types followed by that of nZnO, ZVI, and ZnO, respectively. The removal efficiency rate by all four type particles for Cr was higher than that of Cd and Pb, respectively. In addition to this, the kinetic removal rate of nZVI was also faster than that of nZnO, ZVI, and ZnO, respectively..